Neighborhood socioeconomic status and length of stay after congenital heart disease surgery - Vashist, Sudhir; Dudeck, Brandon S.; Sherfy, Beth; Rosenthal, Geoffrey L.; Chaves, Alicia H. (Frontiers in Pediatrics, 2023)
Background and Objectives Socioeconomic factors are associated with health outcomes and can affect postoperative length of stay after congenital heart disease (CHD) surgery. The hypothesis of this study is that patients from neighborhoods with a disadvantaged socioeconomic status (SES) have a prolonged length of hospital stay after CHD surgery. Methods Pre- and postoperative data were collected on patients who underwent CHD surgery at the University of Maryland Medical Center between 2011 and 2019. A neighborhood SES score was calculated for each patient using data from the United States Census Bureau and patients were grouped by high vs. low SES neighborhoods. The difference of patient length of stay (LOS) from the Society for Thoracic Surgeons median LOS for that surgery was the primary outcome measure. Linear regression was performed to examine the association between the difference from the median LOS and SES, as well as other third variables. Results The difference from the median LOS was −4.8 vs. −2.2 days in high vs. low SES groups (p = 0.003). SES category was a significant predictor of LOS in unadjusted and adjusted regression analyses. There was a significant interaction between Norwood operation and SES—patients with a low neighborhood SES who underwent Norwood operation had a longer LOS, but there was no difference in LOS by SES in patients who underwent other operations. Conclusions Neighborhood SES is a significant predictor of the LOS after congenital heart disease surgery. This effect was seen primarily in patients undergoing Norwood operation.